TEACHING ENGLISH FOR KINDERGARTEN STUDENTS (A CASE STUDY AT TK AL-AZHAR MOJOKERTO) - RAHAYU, ISMIA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Teaching English for kindergarten students is different from high levelschool students. The teacher should use appropriate technique and method tomake the students interested in learning English. The aim of teaching and learningEnglish for kindergarten students is to introduce English in early age so that theywill be familiar with English. This study was conducted to investigate the techniques and methods usedby the English teacher in TK Al-Azhar, the materials used to support teaching andlearning English, and the students’ participat ion in learning English. This researchwas conducted using qualitative research design, and the instrument used wereinterview, observation, and document analysis. The findings of this research were (1) the technique and method used bythe teacher could attract kindergarten students to learn English well. The teachingtechnique used by the teacher were singing songs, sensing using picture cards toexplain the material, imitat ing the teacher’s pronunciat ion, drilling the studentspronunciation, giving test to the students; (2) the supporting material to teach thekindergarten students were textbooks and picture series. While, the media forteaching English were songs created by the teacher or obtained from training, thepicture cards taken from the picture series or students’ handbook and real object.(3) The students are enthusiastic and happy in learning English. They were activein class and quickly understood what the teacher taught. In conclusion, the use of picture cards and songs are helpful for the teacherto attract the students and make the class more fun. Besides, applying theappropriate methods and techniques in teaching English can achieve the target inteaching English for kindergarten students. The researcher suggests that furtherstudy analyzes the technique of teaching English using story telling or short movieto enrich kindergarten students’ vocabulary. Keywords: SLA, Teaching English, Technique and Teaching Method, Supporting Material, Students Participation.